Model for superconductivity in optimally doped electron cuprates: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Geballe, T. H.; Moyzhes, B. Y. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The very anomalous normal state properties and superconductivity of electron-doped supercon-ductingcuprates with the T* structure are discussed. The literature values of high mobilities for electrons and holes are explained by the electrons and holes existing in different layers. The annealingprocedures necessary for superconductivity produce oxygen-vacancy negative-U pairing centers. The relative insensitivity of Tc to the annealing condition is attributed to stabilization of the chemicalpotential near the middle of the narrow oxygen band formed by oxygen vacancies where the electronic entropy is large.